The Impact of ASEAN Economic Community on the Textile and Clothing Industry in Indonesia - Edi Sutarta, Agustinus; Girik Allo, Albertus (Jurnal Ekonomi Kuantitatif Terapan; 2019: Vol. 12, No.1, Februari 2019 (pp. 1-107)DO - 10.24843/JEKT.2019.v12.i01.p03, 2019)
ASEAN Economic Community (AEC) has implemented in 2015. Implementation of AEC means there will be freedom of movement of goods, labor, and capital among the members of the AEC. This study aims to evaluate the impact of the implementation of AECs in the textile and clothing (T&C) industry in Indonesia. We used computable general equilibrium (CGE) model with model GTAP version 8 to evaluate this impact. This study showed that the country will enjoy the greatest benefits of the liberalization of the T&C industry of AEC regions are Vietnam, followed by Thailand and Indonesia.